MINERAL COMPOSITION AND STRUCTURAL FEATURES OF JEWELER AMMONITES FROM KOSTROMA REGION - D. A. Petrochenkov (Известия высших учебных заведений: Геология и разведка, 2017)
Detailed mineralogical examination of ammonites of jewelry quality has been carried out by means of radiographical, X-ray microanalyses and electronic microscopy. The ammonites consist mainly of calcite, apatite and some cells are constituted of phosphorite. The walls and shell’s septums consist of apatite and calcite, which have replaced original aragonite and maintain inclusions of pyrite of globular shape, aluminosilicate and organic matter. Dispersed apatite determines the black color of walls and shell’s septums. The color and transparency of the calcite, filling up the shell’s chambers, are determined by the quantity of micropores and microinclusions, mainly of apaTite. Ammonites from Kostroma region by its decorative and technology characteristics will be able to use widely in jewelry and interior articles.